2009
DOI: 10.1111/j.1365-2672.2009.04212.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon and nitrogen sources on bovicin HC5 production byStreptococcus bovisHC5

Abstract: Aims:  To investigate the effect of media composition and agroindustrial residues on bovicin HC5 production by Streptococcus bovis HC5. Methods and Results:  Batch cultures of S. bovis HC5 were grown in basal medium containing different carbon and nitrogen sources. The activity of cell‐free and cell‐associated bovicin HC5 was determined in culture supernatants and acidic extracts obtained from cell pellets, respectively. Streptococcus bovis HC5 produced bovicin using a variety of carbon and nitrogen sources. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
3
3
0
1
Order By: Relevance
“…Furthermore, P. acidilactici TP-6 was able to utilize an array of carbon sources for its growth. This is in agreement with the findings reported by several studies, whereby various LAB were demonstrated to have the capability to utilize various carbon sources for their growth [55][56][57].…”
Section: Run a B C D E F G H J K L M N O P Q R S T Usupporting
confidence: 93%
“…Furthermore, P. acidilactici TP-6 was able to utilize an array of carbon sources for its growth. This is in agreement with the findings reported by several studies, whereby various LAB were demonstrated to have the capability to utilize various carbon sources for their growth [55][56][57].…”
Section: Run a B C D E F G H J K L M N O P Q R S T Usupporting
confidence: 93%
“…The results from the effects of carbon sources on bacteriocin-inhibitory activity of the postbiotic metabolites produced by L. plantarum I-UL4 are also in agreement with findings from other studies, where glucose was reported to be the preferential carbon source for bacteriocin production by Streptococcus bovicin (Carvalho et al, 2008) and Lactobacillus sakei (Todorov et al, 2012). However, other carbon sources which support optimal bacteriocin production have also been reported for other LAB strains (Cheigh et al, 2002;Drosinos et al, 2005, Wang et al, 2010.…”
Section: Determination Of Optimum Carbon Sourcesupporting
confidence: 81%
“…Indeed, the effect of yeast extract as a single organic nitrogen source on the improvement of bacteriocin activity has been reported for Streptococcus bovis (Carvalho et al, 2008), Lactobacillus rhomanus (Sarika et al, 2010) and Lactobacillus sakei (Todorov et al, 2012). It is likely that the free amino acids and growth factors present in the yeast extract (Aasen et al, 2000) contributed to the stimulatory effect on the production of bacteriocin-inhibitory compounds by L. plantarum I-UL4.…”
Section: Effects Of Different Combinations Of Carbon and Nitrogen Soumentioning
confidence: 99%
“…Because of the growth associated bacteriocin production and the limited number of catabolic pathways, which provide energy to the LAB (substrate level phosphorylation), cell synthesis and the energy demanding bacteriocin production is limited. Several LABs seem to use glucose preferentially for bacteriocin production, and previous studies indicated that Lactococcus lactis, Streptococcus pyogenes, and Streptococcus bovis also preferred glucose for nisin Z, streptococcin SA-FF22, and bovicin HC5 production, respectively (25)(26)(27). Similarly Leuconostoc mesenteroides and Lactobacillus curvatus preferred glucose as carbon source for bacteriocin production (28).…”
Section: Optimization By Ffdmentioning
confidence: 95%